Aneuploidy correlated 100% with chemical transformation of Chinese hamster cells - Li, Ruhong (The National Academy of Sciences of the USA, 1997)
Aneuploidy or chromosome imbalance is the most massive genetic abnormality of cancer cells. It used to be considered the cause of cancer when it was discovered more than 100 years ago. Since the discovery of the gene, the aneuploidy hypothesis has lost ground to the hypothesis that mutation of cellular genes causes cancer. According to this hypothesis, cancers are diploid and aneuploidy is secondary or nonessential. Here we reexamine the aneuploidy hypothesis in view of the fact that nearly all solid cancers are aneuploid, that many carcinogens are nongenotoxic, and that mutated genes from cancer cells do not transform diploid human or animal cells. By regrouping the gene pool—as in speciation—aneuploidy inevitably will alter many genetic programs. This genetic revolution can explain the numerous unique properties of cancer cells, such as invasiveness, dedifferentiation, distinct morphology, and specific surface antigens, much better than gene mutation, which is limited by the conservation of the existing chromosome structure. To determine whether aneuploidy is a cause or a consequence of transformation, we have analyzed the chromosomes of Chinese hamster embryo (CHE) cells transformed in vitro. This system allows (i) detection of transformation within 2 months and thus about 5 months sooner than carcinogenesis and (ii) the generation of many more transformants per cost than carcinogenesis. To minimize mutation of cellular genes, we have used nongenotoxic carcinogens. It was found that 44 out of 44 colonies of CHE cells transformed by benz[a]pyrene, methylcholanthrene, dimethylbenzanthracene, and colcemid, or spontaneously were between 50 and 100% aneuploid. Thus, aneuploidy originated with transformation. Two of two chemically transformed colonies tested were tumorigenic 2 months after inoculation into hamsters. The cells of transformed colonies were heterogeneous in chromosome number, consistent with the hypothesis that aneuploidy can perpetually destabilize the chromosome number because it unbalances the elements of the mitotic apparatus. Considering that all 44 transformed colonies analyzed were aneuploid, and the early association between aneuploidy, transformation, and tumorigenicity, we conclude that aneuploidy is the cause rather than a consequence of transformation.